INFORMED CONSENT DALAM PELAYANAN KESEHATAN - Adriana Pakendek Adriana Pakendek (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Abstract:   It is a must to apply the informed consent in public health service, particularly in a hosptal. As a matter of fact, some medical patients or the  representative does not comprehend the term informed consent due to the ineffective communication between the patient and physician. Whereas, a doctor should have a legal informed consent to execute medical action from the patient, otherwise she/he would experience a question of law; private and punitive law as well as indisciplinary punishment. A petient is able to deny an informed consent, yet it is identified as an informed refusal. However, the patient must be responsible for any medical impacts in the future. In this case, a doctor is free from any legal actions as the result of consent refusal of patient.   Key Words: informed consent, pasien dan dokter